Produção de lipopeptídeos e glicolipídeos a partir da bioconversão do co-produto da produção do biodiesel - Sousa, Juliana Rabelo de (2012)
Biosurfactants are a surface-active chemical compounds synthesized by microorganisms. These compounds have many advantages when compared to their chemically synthesized counterparts as specific action, low toxicity, higher biodegradability, effectiveness at extreme temperatures, pH and strength ionic. They appear as promising candidates to replace chemical surfactants produced from petrochemicals. The use of renewable and low cost substrates such as agro based industrial wastes is one of the attractive strategies for economical large scale biosurfactants production. In this work, it was evaluated glycerol, a co-product of biodiesel production, as carbon source for biosurfactant production. Two microorganisms, Pseudomonas aeruginosa MSCIC02 and Bacillus subtilis LAMI009, both isolated from environmental sources, were used thorough this work. In the first part of the work experiments were carried out in shake flasks using P. aeruginosa. The results showed that the increase in nitrogen source (sodium nitrate) and the decrease in the carbon source (glycerin) favored rhamnolipids production. In the range studied, the maximum biosurfactant concentration obtained was 2.3 g⋅L-1 (C/N ratio 12). The effect of nitrogen concentration on the biosynthesis of rhamnolipids and pH behavior as a function of the nitrate concentration in the cultures indicated that this strain probably carried a denitrification route favoring the production of rhamnolipids. Experimental runs carried out in bioreactor indicated that the integrated process of production and separation/concentration by fractionation in bubble column equipment caused many operation problems, such as the drag cell, and reducing the concentration of rhamnolipids to 0.4 g⋅L-1in the reaction medium. The kinetics of product formation was evaluated by two models. The Luedeking-Piret model was not able to represent the process. The model proposed by MERCIER et. al. (1992) could adequately describe the rhamnolipids production from P. aeruginosa strain. Emulsifying capacity of the cell-free culture medium was assessed by the emulsification index (EI24). The biosurfactant produced was able to emulsify vegetable oils as well as mineral oils. EI24 greater than 55% was reached. In the second part of the work experimental data from Bacillus subtilis LAMI009 cultivated in shake flasks showed that the growth of this strain was dependent on iv the medium supplementation with yeast extract. A change in culture medium was implemented in order to reduce the length of the lag phase. The use of inorganic nitrogen sources showed that both ammonium nitrate and ammonium sulphate reached similar values of surfactin concentration and volumetric productivity. It was obtained 35 mg⋅L-1 and 6.1 mg⋅L-1⋅h-1, respectively. Surface tension of the cell-free culture medium was similar for both nitrogen sources. The minimal value obtained was 29.7 mN⋅m-1. Sodium nitrate was found to be an adequate nitrogen source for cell growth. However, in these assays low productivity and low surface tension reduction were obtained when compared to the other nitrogen sources evaluated. The supplementation of the culture medium with yeast extract improves the surfactin concentration (60.0 mg⋅L-1) and volumetric productivity (5.2 mg⋅L-1⋅h-1). In this assay the surface tension reached 28.1 mN⋅m-1. The inoculum size had a great influence on cell growth and production of surfactin. When 2% (v/v) of inoculum was used the surfactin concentration and volumetric productivity obtained were 148.2 mg⋅L-1 e 14.22 mg⋅L-1⋅h-1, respectively. The search for genes responsible for production of lipopeptides surfactin and iturine indicated the presence of the genes lpa14 and ituD in B. subtilis LAMI009 genome. Analysis of the chromatography profile of methanol extracts of the lipopeptides from culture medium with ammonium nitrate and sodium nitrate as nitrogen source showed characteristic peaks of the surfactin and iturine. Thereby, it is believed that this strain is a co-producer of both surfactin and iturine. Emulsifying capacity of the cell-free culture medium showed higher stability with the media that employed ammonium nitrate and sodium nitrate as nitrogen source. It was obtained EI24 of 65% with n-hexadecane and 45% with kerosene. The acid precipitation of biosurfactant from the cell-free culture medium showed that this prepurification step promoted an increase in the emulsifying capacity of the mixture of lipopeptides synthesized by B. subtilis LAMI009. The aqueous solution of crude biosurfactant was able to emulsify naphthenic oils, vegetable oils, and an aromatic hydrocarbon. Values of EI24 greater than 65% were obtained. Emulsions formed with naphthenic oils were more stable according to droplet-size distribution. The smaller the size of droplets, the more stable was the emulsion.